Gαi protein subunit: A step toward understanding its non-canonical mechanisms - Villaseca, Soraya; Romero, Gabriel; Ruiz, María J.; Pérez, Carlos; Leal, Juan I.; Tovar, Lina M.; Torrejón, Marcela (Frontiers in Cell and Developmental Biology, 2022)
The heterotrimeric G protein family plays essential roles during a varied array of cellular events; thus, its deregulation can seriously alter signaling events and the overall state of the cell. Heterotrimeric G-proteins have three subunits (alpha, beta, gamma) and are subdivided into four families, Galphai, Galpha12/13, Galphaq, and Galphas. These proteins cycle between an inactive Galpha-GDP state and active Galpha-GTP state, triggered canonically by the G-protein coupled receptor (GPCR) and by other accessory proteins receptors independent also known as AGS (Activators of G-protein Signaling). In this review, we summarize research data specific for the Galphai family. This family has the largest number of individual members, including Galphai1, Galphai2, Galphai3, Galphao, Galphat, Galphag and Galphaz, and in most cases constitutes the bulk of expressed G proteins alpha subunits in a given tissue or cell. Galphai was initially described by its inhibitory function over adenylyl cyclase activity, decreasing cAMP levels. Interestingly, today Gi family G-protein have been reported to be importantly involved in the immune system function. Here, we discuss the impact of Galphai on non-canonical effector proteins, such as c-Src, ERK1/2, phospholipase-C (PLC), and proteins from the Rho GTPase family members, all of them essential signaling pathways regulating a wide range of physiological processes.